FRI0550 CAN CYTOKINE GENE POLYMORPHISMS BE USEFUL FOR THE THERAPEUTIC CHOICE IN JAPANESE PATIENTS WITH RHEUMATOID ARTHRITIS?. (2nd June 2020) - Tsujimoto, S.; Shigesaka, M.; Tanaka, A.; Ozaki, Y.; Ito, T.; Inaba, M.; Nomura, S.
Abstract : Background: Rheumatoid arthritis (RA) is a common autoimmune disease. It is characterized by systemic synovitis with bone erosion and joint cartilage degradation(1). Production of autoantibody is important for autoimmune disease. Cytokines play crucial roles in its pathogenesis(2). SNP distribution varies between races. Few studies have examined SNP targeted at Japanese patients. The analysis of cytokine gene polymorphisms is important factor of pathophysiology and treatment. Objectives: This analysis was aimed to investigate the association between cytokine gene polymorphisms and autoantibody and therapeutic response in Japanese RA patients. Methods: This study subjects consisted of 100 RA patients and 50 healthy controls. We extracted data on patient sex, age, disease duration, rheumatoid factor (RF), anti cyclic citrullinated peptide (anti-CCP) antibody and therapeutic response including methotrexate (MTX) and biological DMARDs. Genomic DNA was isolated from peripheral blood, these were genotyped for TNFα, TGFβ1, IL-6, IL-10 and IFNγ polymorphisms. We analyzed these data using a chi-square test. Results: IL-10 (-819 C/T and -592 C/A) revealed that there were significant decrease in the frequency of IL-10 (-819) CC genotype and (-592) CC genotype as compared to controls in RA patients. Genotyping of IL-10 showed that there was significant decrease ACC/ACC genotype (Table 1 ). IFNγ (+874 A/T) revealed that there was significant decrease in the frequency of TT genotype as compared to controls (Table 1 ). No significant differences in TNFα, TGFβ1 and IL-6 genotypes and alleles frequency were observed between RA patients and control. TGFβ1 (+869 A/T) in patients with anti-CCP antibody positive revealed that there was significant decrease in the frequency of TT genotype as compared to patients with anti-CCP antibody negative (Table 2 ). No significant association between RF and any cytokine gene polymorphism. Analyzing cytokine gene polymorphisms could be useful for treatment with MTX and biological DMARDs. Table 1. Table 2. Conclusion: IL-10 (-819 C/T, -592 C/A) and IFNγ (+874 A/T) polymorphism might be related to RA in Japanese population. In addition, TGFβ1 (+869 A/T) polymorphism might be associated with the production of anti-CCP antibody. These results suggest that the analyzing cytokine gene polymorphisms may offer promise as useful factors in the choice of treatment for Japanese RA patients. References: [1] Scott DL, Wolfe F, Huizinga TW. Rheumatoid arthritis. Lancet. 2010; 376: 1094–108. [2] McInnes IB, Schett G. Cytokines in the pathogenesis of rheumatoid arthritis. Nat Rev Immunol. 2007 Jun;7(6):429-42. Disclosure of Interests: None declared